Genetic and functional analysis of the human immunodeficiency virus (HIV) type 1-inhibiting F12-HIVnef allele - D’Aloja, Paola; Santarcangelo, Anna Claudia; Arold, Stefan; Baur, Andreas; Federico, Maurizio (Journal of General Virology, 2001)
The primary human immunodeficiency virus type 1 (HIV-1) Nef mutant F12-HIVNef is characterized by three rare amino acid substitutions, G140E, V153L and E177G. It was reported previously that the expression of F12-HIVNef in the context of the highly productive NL4-3 HIV-1 strain blocks virus replication at the level of virus assembly and/or release by a mechanism depending on the presence of the CD4 intracytoplasmic tail. Here, it is reported that NL4-3 HIV-1 strains expressing F12-HIVnef alleles that were back-mutated in each amino acid substitution readily replicated in CD4+ cells. Attempting to correlate possible functional alterations with antiviral effects, both F12-HIVNef and its back mutants were tested in terms of well-characterized markers of Nef expression. Both F12-HIVNef and its G177E back mutant did not down-regulate CD4 as the consequence of a greatly reduced rate of CD4 internalization. On the other hand, F12-HIVNef as well as the E140G and L153V back mutants failed to activate the p62 Nef-associated kinase (p62NAK). Thus, only F12-HIVNef was defective in both accelerated rates of CD4 internalization and p62NAK activation, whereas at least one Nef function was restored in all of the back mutants. Infection of cells expressing Nef-resistant CD4 molecules with HIV-1 strains encoding F12-HIVNef back mutants showed that both the lack of accelerated CD4 endocytosis and an, as yet, still unidentified function are required for the F12-HIVNef inhibitory phenotype. These results provide a detailed functional analysis of the F12-HIVnef allele and support the idea that both CD4 accelerated internalization and p62NAK activation are part of the essential steps in the virus replication cycle.